Gaya Kepemimpinan Kolaboratif Kepala Sekolah dalam Membangun Lingkungan Kerja yang Kolaboratif - Fadilatul Laila; Elva Zahrotunnaqiyah; Veby Anggareni; Fakhrudin Ultsa; Cucu Atikah (Universitas Negeri Malang, 2025)
Abstract: The school principal plays a strategic role in directing the sustainability of the educational process, particularly in ensuring the creation of an effective, positive, and collaborative work environment. Curriculum changes and the increasing complexity of educational challenges require principals to implement a collaborative leadership style, namely leadership that involves teachers, educational staff, parents, and other stakeholders in the decision-making process. Collaborative leadership is considered capable of addressing the needs of schools in an era of change, as it promotes open communication, teamwork, innovation, and shared responsibility in dealing with various challenges. In addition, a collaborative work environment developed through continuous coaching, joint professional development, and a supportive school climate has been proven to enhance teachers’ work motivation, job satisfaction, and professionalism. Principals need to ensure transparent and open communication among all staff members. They also need to provide guidance and support for teachers to participate in professional development activities that involve collaboration among teachers. The impact of a collaborative work environment facilitated by the principal can be seen in increased teacher motivation, job satisfaction, and professionalism. This study aims to describe the implementation of a principal’s collaborative leadership style, focusing on forms of teachers’ collaborative behavior and the strategies used by principals to build a collaborative work environment. This study employs a qualitative research method and provides a general overview of the principal’s collaborative leadership style in building a collaborative work environment. Keywords: Leadership style; Work environment; Collaborative Abstrak: Kepala sekolah memiliki peran strategis dalam mengarahkan keberlangsungan proses pendidikan, terutama dalam memastikan terciptanya lingkungan kerja yang efektif, positif, dan kolaboratif. Perubahan kurikulum serta meningkatnya kompleksitas tantangan pendidikan menuntut kepala sekolah menerapkan gaya kepemimpinan yang kolaboratif, yaitu kepemimpinan yang melibatkan guru, tenaga kependidikan, orang tua, dan pemangku kepentingan dalam proses pengambilan keputusan. Gaya kepemimpinan kolaboratif dipandang mampu menjawab kebutuhan sekolah di era perubahan karena mendorong komunikasi terbuka, kerja tim, inovasi, dan rasa tanggung jawab bersama dalam menghadapi berbagai persoalan. Selain itu, lingkungan kerja kolaboratif yang dibangun melalui pembinaan berkelanjutan, pengembangan profesional bersama, serta iklim sekolah yang mendukung terbukti meningkatkan motivasi kerja, kepuasan, serta profesionalisme guru. Kepala sekolah perlu memastikan komunikasi yang transparan dan terbuka di antara seluruh pegawai. Kepala sekolah perlu memberikan pembinaan kepada guru untuk mengikuti kegiatan seperti pengembangan profesional yang melibatkan kolaborasi antar guru. Dampak lingkungan kerja kolaboratif yang difasilitasi oleh kepala sekolah dapat terlihat dari aspek motivasi, kepuasan kerja, dan profesionalisme guru. Penelitian ini bertujuan untuk mendeskripsikan penerapan gaya kepemimpinan kolaboratif kepala sekolah dengan fokus pada bentuk perilaku kolaboratif guru serta strategi kepala sekolah dalam membangun lingkungan kerja yang kolaboratif. Penelitian ini menggunakan metode kualitatif. Penelitian ini memberi gambaran umum terkait gaya kepemimpinan kolaboratif kepala sekolah dalam membangun lingkungan kerja yang kolaboratif. Kata kunci: Gaya kepemimpinan; Lingkungan kerja; kolaboratif.